Development of a detector for inertial sensing of positronium at AEḡIS (CERN). Issue 1 (1st November 2022) - Glöggler, L. T.; Caravita, R.; Bergmann, B.; Bonomi, G.; Brusa, R. S.; Burian, P.; Camper, A.; Castelli, F.; Cheinet, P.; Comparat, D.; Consolati, G.; Doser, M.; et al.
Abstract : The primary goal of the AEgIS collaboration at CERN is to measure the gravitational acceleration on neutral antimatter. Positronium (Ps), the bound state of an electron and a positron, is a suitable candidate for a force-sensitive inertial measurement by means of deflectometry/interferometry. In order to conduct such an experiment, the impact position and time of arrival of Ps atoms at the detector must be detected simultaneously. The detection of a low-velocity Ps beam with a spatial resolution of (88 ± 5) μm was previously demonstrated [1]. Based on the methodology employed in [1] and [2], a hybrid imaging/timing detector with increased spatial resolution of about 10 μm was developed. The performance of a prototype was tested with a positron beam. The concept of the detector and first results are presented.